Perception of Professional Practices from the voice of the student body of Pedagogy - Rosario Ordóñez-Sierra; Mª Teresa Gómez-del-Castillo-Segurado; Margarita Rodríguez-Gallego (Revista d'Innovació Docent Universitària, 2025)
This study highlights the importance of the practicum in the training of education professionals, since it is a key moment for students to reach the specific competences of the profession in an active and reflective manner. The main aim of research in this field is to assess the pedagogy students’ perception of the blog, videoconference, and peer mentoring as effective tools for reflection and communication in monitoring and evaluating professional practices. The design/methodology about the evaluation of students’ perception was conducted using a mixed design, employing both quantitative and qualitative methods. It involved an already validated online questionnaire and individual blog entries submitted by the 131 participants.